A manual for writers of term paper, theses y and dissertations - Turbian, Kate L (Estados Unidos | ESTADOS UNIDOS The University of Chicago Press / Chicago, 1996)
Contents: Parts of the paper; Abbreviations and numbers; Spelling and puntuation; capitalization, Italics, and quotation marks; Quotations; Tables; Ilustrations; notes
Sin Especificar
Donado por el Área Post-Grado CIRA-UNAN
Keywords: Investigación-Manuales | Imvestigación cientifica-Metodología